Synthesis and cytotoxicity of carbon nanotube/hydroxyapatite in situ composite powders prepared by chemical vapour deposition. (May 2014) - Li, H.; Zhang, N.; Wang, X.; Geng, X.; Yang, X.; Wang, H.; Li, B.; Liang, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Carbon nanotube (CNT)/hydroxyapatite (HA) composite powders were successfully synthesised in situ by chemical vapour deposition of methane. The effects of different catalytic metals (Fe, Ni and Co) on yield, morphology and structure of CNTs were studied. The cytotoxicity of CNT/HA composite powders towards mouse fibroblast cells was investigated by in vitro cell culture test. The results show that Fe and Ni as catalysts are more favourable for the formation of CNT/HA composite powders than Co as catalyst, achieving excellent dispersion of CNTs in HA matrix, which indicates that these CNT/HA in situ composite powders can be directly applied to prepare bulk composite. The results of cytotoxicity test indicate that, compared with commercial CNT and CNT(Ni)/HA composite powders, the CNT(Fe)/HA in situ composite powder has no obvious cytotoxicity, which is more suitable to prepare CNT/HA composite for medical applications. Therefore, the method described in this paper is of great potential to realise the preparation of HA matrix composite with evenly dispersed CNTs, resulting in good mechanical and biological properties.